Laparoscopic inguinal hernia repair-TAPP versus TEP: Results of 301 consecutive patients - Göksoy, Beslen; Yılmaz, Gökhan; Azamat, İbrahim Fethi; Özata, İbrahim Halil; Duman, Kazım (World Journal of Surgery, 2021)
Introduction: Transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) hernia repair are the two most commonly used techniques in laparoscopic inguinal hernia repair, and the results of comparative studies are conflicting. The objective of this study is to compare the two methods in unilateral inguinal hernia repair. Materials and methods: The data of consecutive patients who underwent TEP and TAPP due to unilateral inguinal hernia between December 7, 2017, and March 15, 2020, were analyzed retrospectively. The primary outcome was to compare the clinical outcomes of the two techniques in terms of complications, conversion, pain, and operative time. The secondary outcome was recurrence rates. Results: A total of 301 (TEP n=234, TAPP n=67) patients were included in the study. The mean age was 43 years, and the follow-up period was two years. The groups were similar in terms of demographic characteristics and hernia type. The mean operative time was longer in the TAPP group than in the TEP group (67 min and 58 min, p=0.007). The recurrence rate was 4.3% in the TEP group and 5.9% in the TAPP group (p>0.05). The conversion rate was 6% in both groups. In total, 19 (6.3%) patients had intraoperative complications (TEP n=16, TAPP n=3), and 23 (7.6%) patients had postoperative complications (TEP n=16, TAPP n=7). Both intraoperative and postoperative complication rates were similar between the groups (p=0.31 and p=0.051, respectively). The early postoperative pain was less in the TEP group (p=0.004). Conclusion: Less early postoperative pain and shorter operative time were detected in patients who underwent TEP.
Keywords: Repair-TAPP Versus TEP; Inguinal Hernia; Laparoscopic